Analisis pengaruh elemen Intellectual Capital terhadap kinerja Keuangan (Studi pada BUMN yang terdaftar di BEI). - LINGGO AJI PAMBUDI (AKT 13 UMY 231, 2013)
This study aims to analyze the influence that proxy element with Intellectual Capital Intellectual Capital Value Added ( VAICTM ) the company's financial performance as measured by return on assets ( ROA ) . VAICTM elements consist of Value Added Human capital ( VAHU ) , Structural Capital Value Added ( STVA ) , and Value Added Capital employed ( VACA ) . The population used in this study is a state-owned company listed on the Indonesia Stock Exchange in 2008-2012. Sampling was conducted using a purposive sampling method in order to obtain the 70 companies that will be used as a sample . This hypothesis was tested using multiple linear regression models . Hypothesis testing is done using simultaneous significance test ( F test ) and partial significance test ( t test ) with Î± = 5 % . F test results indicate that the Value Added Human capital ( VAHU ) , Structural Capital Value Added ( STVA ) , and Value Added Capital employed ( VACA ) have significant impact together on financial performance . T-test results show that Structural Capital Value Added ( STVA ) has no effect on financial performance . Meanwhile , the Human Capital Value Added ( VAHU ) and Value Added Capital employed ( VACA ) positive effect on financial performance . Keywords : Human Capital Value Added ( VAHU ) , Structural Capital Value Added ( STVA ) , Value Added Capital employed ( VACA ) , Financial Performance , Return on Assets ( ROA ) .